2020
DOI: 10.1021/acsnano.9b07430
|View full text |Cite
|
Sign up to set email alerts
|

Surface Energy Change of Atomic-Scale Metal Oxide Thin Films by Phase Transformation

Abstract: Fine-tuning of the surface free energy (SFE) of a solid material facilitates its use in a wide range of applications requiring precise control of the ubiquitous presence of liquid on the surface. In this study, we found that the SFE of rare-earth oxide (REO) thin films deposited by atomic layer deposition (ALD) gradually decreased with increasing film thickness; however, these changes could not be understood by classical interaction models. Herein, the mechanism underlying the aforesaid decrease was systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Among these films, most of the materials exhibit hydrophilic properties, whereas In 2 O 3 presents the highest WCA, revealing its hydrophobicity. SnO 2 has a highly hydrophilic surface, retaining a tightly bound hydration layer, which can passively repel foulants such as hydrophobic organic molecules and oils. , A previous study of ALD Y 2 O 3 found that the WCA increased with increasing film thickness from ∼42° at 3 nm to 100° at 50 nm due to the evolution in film crystallinity with thickness . Our finding of WCA = 57.3° at 10 nm Y 2 O 3 is consistent with this previous study.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Among these films, most of the materials exhibit hydrophilic properties, whereas In 2 O 3 presents the highest WCA, revealing its hydrophobicity. SnO 2 has a highly hydrophilic surface, retaining a tightly bound hydration layer, which can passively repel foulants such as hydrophobic organic molecules and oils. , A previous study of ALD Y 2 O 3 found that the WCA increased with increasing film thickness from ∼42° at 3 nm to 100° at 50 nm due to the evolution in film crystallinity with thickness . Our finding of WCA = 57.3° at 10 nm Y 2 O 3 is consistent with this previous study.…”
Section: Resultssupporting
confidence: 91%
“…Figure S19 shows that 7.1 and 15.6 nm ZrO 2 films, for example, have similar surface-charge properties. A previous study found a distinct correlation between the WCA and thickness of ALD Y 2 O 3 films and attributed this variation in surface properties to changes in the crystallinity of the ALD Y 2 O 3 coatings . The Si native oxide and the ALD SiO 2 coatings are amorphous as-deposited, so the crystallinity does not change with thickness.…”
Section: Resultsmentioning
confidence: 87%
“…12 Common protocols, however, need complex and expensive processes to fabricate microstructures. Also, to coat with low-surface-energy materials, processes such as chemical vapor deposition, 13 atomic layer deposition, 14,15 electrodeposition, 16 calcination, 17 and so forth have been adopted, 18 but these are complex for practical applications where a hydrophobic function is required. On the other hand, several industrial-friendly techniques have been also introduced such as in-liquid functionalization 19 and spray coating, 20,21 offering the expansion of applicability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The depth profile measurements (figure S7) highlighted that under the aforementioned conditions, a new steady state has been established, having higher degree of oxidation in subsurface layers than on the Ni/NiO surface. This runs counter to the expected trend in which oxide species in vacuum diffuse and accumulate on the surface of the metal due to their lower surface free energy [50,51]. This result can be rationalized by considering that the stronger interaction of CO 2 with Ni 0 species establish a new equilibrium that inhibits the diffusion of oxygen from the inner layers to the outer shell.…”
Section: Correlation Of Spectroscopic Electrochemical and Gas Phase R...mentioning
confidence: 81%